(untitled) (Journal of Laboratory Animal Science, 2024)
Pinworm infestation is more common in most conventional colonies of laboratory rodents. They usually do not exhibit any clinical signs and no adverse effects have been reported on reproduction in infested animals, although, there is an inverse relationship between bodyweight and degree of infestation in newly weaned rodents. It has been reported that oxyurid infestations influence experimental results and also interfere with research goals in number of ways. The prevalence of pinworms in rodent population depends on many factors, including environmental load, gender, age, strain, and immune status. Unlike many common viral diseases of laboratory mice, pinworm infestations can be treated. A rederivation program is highly recommended if other pathogens are present in the colony. Present study was carried out to evaluate the effective treatment regimen for oxyurid infestation. Rodent colonies were screened for adult oxyurid worms or eggs by cellophane tape or flotation method. This screening revealed the presence of pinworm in mouse and rat colonies. Treatment regimen included administration of combinations of fenbendazole and praziquantel for group I at the rate of 150 mg/kg and 50 mg/kg respectively for 24 days through drinking water. Piperazine and ivermectin was administered for group II at the rate of 10.8 mg/mL for 14 days and 0.01mg/mL for next 14 days respectively through drinking water. No oxyurids were found in the colony after 28 days of treatment in group II. It was concluded based on the treatment regimen that piperazine and ivermectin combination was more effective in complete eradication of oxyurids in rodents.